Green-light mechanoluminescent material as well as preparation method and application thereof
By doping Al2O3 in Ca5Ga6O14:Tb3+ material, a green-light electroluminescent material with high trap concentration was prepared, which solved the problems of low luminescent intensity and poor stability of the flexural electroluminescent material in the prior art, and achieved no pre-irradiation. Highly effective electroluminescence and long-term luminescence, suitable for crack detection and other applications.
Patent Information
- Application Number
- CN202411730053.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-11-29
AI Technical Summary
Existing powerful electroluminescent materials have low luminescence intensity, low sensitivity and poor stability, and require pre-irradiation to produce electroluminescence, which limits their development and application.
By doping Al2O3 in Ca5Ga6O14:Tb3+ material, a green-light electroluminescent material with the chemical formula Ca5Ga6-XAlXO14:Tb3+ was prepared, and calcined using specific molar ratios of H3BO3, Al2O3, CaCO3, Ga2O3 and Tb4O7 to form a high trap concentration and Deep trap material that allows it to charge and generate force-luminescence under natural light.
Achieve high-force electroluminescent intensity, high sensitivity and long-term luminescence without pre-irradiation, and has good stability in green-light electroluminescent materials, which can maintain luminescence performance for a long time under dark conditions and exhibit crack detection. Excellent optical performance.
Smart Images

Figure CN119220254A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid luminescent materials, and in particular relates to a green light mechanoluminescent material and a preparation method and application thereof. Background Art
[0002] Mechanoluminescent materials have been widely studied in recent years. Materials can be made to emit light by applying pressure, friction or other forms of force to them. This type of luminescent material that relies on force excitation is an energy-saving green smart material. However, current mechanoluminescent materials have low luminous intensity, low sensitivity, and poor stability. They require pre-irradiation with ultraviolet rays or X-rays for charging to produce mechanoluminescence, which seriously hinders the development and application of mechanoluminescent materials. Summary of the invention
[0003] In view of this, the purpose of the present invention is to provide a green light mechanoluminescent material and its preparation method and application. The green light mechanoluminescent material of the present invention does not require pre-irradiation, has high mechanoluminescent intensity and high sensitivity, and has a long mechanoluminescent time and good stability without charging conditions.
[0004] The present invention provides a green light luminescent material, the chemical formula of which is Ca5Ga 6-X Al X O 14 :Tb 3+ , where X=0~1.6, and X is not 0.
[0005] Preferably, X=0.8~1.6.
[0006] The present invention also provides a method for preparing the green light mechanoluminescent material described in the above technical solution, comprising the following steps: H3BO3, Al2O3, CaCO3, Ga2O3 and Tb4O7 are mixed and calcined to obtain the green light electroluminescent material. Preferably, the molar ratio of H3BO3, Al2O3, CaCO3, Ga2O3 and Tb4O7 is (0.001~0.003): (0.1~0.8): (4.5~5.5): (2.2~2.9): (0.01~0.09).
[0007] The present invention also provides the use of the green mechanoluminescent material described in the above technical solution or the green mechanoluminescent material obtained by the above preparation method in crack detection.
[0008] The present invention also provides a mechanoluminescent composite material, comprising the following raw materials in parts by weight: 3-5 parts of green light luminescent material, 5-7 parts of molding agent and 0.9-1.1 parts of curing agent; The green mechanoluminescent material is the green mechanoluminescent material described in the above technical solution or the green mechanoluminescent material obtained by the above preparation method.
[0009] Preferably, the molding agent comprises polydimethylsiloxane and / or epoxy resin.
[0010] The present invention also provides a method for preparing the mechanoluminescent composite material described in the above technical solution, comprising the following steps: The green light mechanoluminescent material, the molding agent and the curing agent are mixed and cured to obtain the mechanoluminescent composite material.
[0011] Preferably, the curing temperature is 65-75° C. and the curing time is 40-60 minutes.
[0012] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a green light luminescent material, the chemical formula of which is Ca5Ga 6-X Al X O 14 :Tb 3+ , where X = 0~1.6, and X is not 0. The present invention dopes Al into Ca5Ga6O 14 :Tb 3+ The green light mechanoluminescent material obtained has abundant traps in the material. The high trap concentration and deep traps enable the material to be charged under natural light, store electrons, and generate mechanoluminescence. The green light mechanoluminescent material of the present invention does not require pre-irradiation, has high mechanoluminescence intensity and high sensitivity, and has a long mechanoluminescence time and good stability under non-charging conditions.
[0013] The data of the embodiment show that the mechanoluminescent material of the present invention can still produce obvious mechanoluminescence in the air environment for up to 15 days under dark conditions, and has a continuous mechanoluminescence of up to 0.183 seconds under the instantaneous tensile stress test. The mechanoluminescent material of the present invention has high stability and excellent optical properties, and can still produce obvious mechanoluminescence under a force of 5N when applied to crack detection. The present invention provides a new idea and method for the development of new green smart materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0015] Figure 1 The XRD diffraction patterns of the materials of Comparative Example 1 and Examples 1 to 5 are shown; Figure 2 This is the SEM image of the material of Example 4; Figure 3 The luminous intensity of the materials of comparative example 1 and examples 2 to 5 under the same force; Figure 4 The actual pictures of the material stability test of Comparative Example 1 and Example 4; Figure 5 This is the luminescence intensity and spectrum of the composite material of Application Example 1 at 2~6N; Figure 6 This is a real picture of the luminous intensity of the composite material in Application Example 1 under 2~6N; Figure 7 This is a schematic diagram of application example 1, which shows the application of composite materials in crack detection. DETAILED DESCRIPTION
[0016] The present invention provides a green light luminescent material, the chemical formula of which is Ca5Ga 6-X Al X O 14 :Tb 3+ , where X=0~1.6, and X is not 0.
[0017] In the present invention, unless otherwise specified, the materials and equipment used are commercially available products in the art.
[0018] In the present invention, preferably X=0.8-1.6, specifically 0.2, 0.4, 0.8, 1.2 or 1.6. In the X value range of the present invention, the obtained green light mesoluminescent material has high mesoluminescent intensity and excellent stability.
[0019] In the present invention, the chemical formula of the green light luminescent material is preferably Ca5Ga 6-X Al X O 14 :0.06Tb 3+ , where X=0.2, 0.4, 0.8, 1.2 or 1.6.
[0020] The green light luminescent material of the present invention is Al2O3 doped Ca5Ga6O 14 :Tb 3+ The material, doping with aluminum oxide improves the luminous intensity and stability of the material, can produce mechanoluminescence without pre-irradiation and charging, and can still produce obvious mechanoluminescence in the air environment for up to 15 days under dark conditions. The green light mechanoluminescent material is a columnar crystal.
[0021] The present invention also provides a method for preparing the green light mechanoluminescent material described in the above technical solution, comprising the following steps: H3BO3, Al2O3, CaCO3, Ga2O3 and Tb4O7 are mixed and calcined to obtain the green light electroluminescent material.
[0022] In the present invention, the molar ratio of H3BO3 to CaCO3 is preferably (0.001-0.003):(4.5-5.5), and specifically can be 0.002: 5. The H3BO3 is a co-solvent, which can reduce the calcination (sintering) temperature.
[0023] In the present invention, the molar ratio of Al2O3 to CaCO3 is preferably (0.1-0.8): (4.5-5.5), specifically 0.1: 5, 0.2: 5, 0.4: 5, 0.6: 5 or 0.8: 5. The Al2O3 can adjust the material trap concentration, increase the material's ability to store electrons, and improve the material's luminescence intensity and stability.
[0024] In the present invention, the molar ratio of CaCO3 to Ga2O3 is preferably (4.5-5.5):(2.2-2.9), specifically 5: 3. The CaCO3 and Ga2O3 are the main matrices for preparing green light electroluminescent materials.
[0025] In the present invention, the molar ratio of Tb4O7 to CaCO3 is preferably (0.01-0.09):(4.5-5.5), and specifically can be 0.03:5. 3+ Provide luminescent ions for green light luminescent materials.
[0026] In the present invention, the molar ratio of H3BO3, Al2O3, CaCO3, Ga2O3 and Tb4O7 is preferably (0.001~0.003):(0.1~0.8):(4.5~5.5):(2.2~2.9):(0.01~0.09), specifically 0.002: 0.1: 5:2.9: 0.03, 0.002: 0.2: 5: 2.8: 0.03, 0.002: 0.4: 5: 2.6: 0.03, 0.002: 0.6: 5:2.4: 0.03 or 0.002: 0.8: 5: 2.2: 0.03.
[0027] In the present invention, the calcination preferably further comprises mixing H3BO3, Al2O3, CaCO3, Ga2O3 and Tb4O7 for grinding, and the grinding is preferably carried out in an agate mortar; the particle size of the powder after grinding is preferably not greater than 0.075 mm (through a 200 mesh sieve).
[0028] In the present invention, the calcination temperature is preferably 1150-1250°C, specifically 1200°C, and the holding time is preferably 3-5 hours, specifically 4 hours. The heating rate from room temperature to the calcination temperature is preferably 5-7°C / min, specifically 6°C / min. The present invention preferably places H3BO3, Al2O3, CaCO3, Ga2O3 and Tb4O7 powders in an alumina crucible and performs the calcination in a chamber furnace. During the calcination process, the synthesized Ca5Ga6O 14 :Tb 3+ , while some Al 3+ Replacement of Ga 3+ The calcination preferably includes cooling, and the cooling is preferably carried out along with the furnace.
[0029] The present invention also provides the use of the green mechanoluminescent material described in the above technical solution or the green mechanoluminescent material obtained by the above preparation method in crack detection.
[0030] The present invention also provides a mechanoluminescent composite material, comprising the following raw materials in parts by weight: 3-5 parts of green light luminescent material, 5-7 parts of molding agent and 0.9-1.1 parts of curing agent; The green mechanoluminescent material is the green mechanoluminescent material described in the above technical solution or the green mechanoluminescent material obtained by the above preparation method.
[0031] In the present invention, the molding agent preferably includes polydimethylsiloxane (PDMS) and / or epoxy resin, and more preferably polydimethylsiloxane. The molding agent molds the green mechanoluminescent powder material. In the present invention, polydimethylsiloxane is used as the molding agent, and the composite material can generate obvious mechanoluminescence under a relatively small force.
[0032] In the present invention, the curing agent is preferably the curing agent in the American Dow Corning DC184 silicone rubber. The curing agent promotes the molding of the material. In the embodiment of the present invention, the molding agent and curing agent used are American Dow Corning DC184 silicone rubber (including PDMS matrix and curing agent).
[0033] In the present invention, the mechanoluminescent composite material preferably comprises the following raw materials in parts by mass: 4 parts of green mechanoluminescent material, 6 parts of molding agent and 1 part of curing agent.
[0034] The present invention also provides a method for preparing the mechanoluminescent composite material described in the above technical solution, comprising the following steps: The green light mechanoluminescent material, the molding agent and the curing agent are mixed and cured to obtain the mechanoluminescent composite material.
[0035] In the present invention, the curing temperature is preferably 65-75°C, specifically 70°C, and the curing time is preferably 40-60 minutes, specifically 50 minutes. In the present invention, the green light electroluminescent material, the molding agent and the curing agent are preferably placed in a polytetrafluoroethylene mold and heated in an oven for curing.
[0036] The present invention applies composite materials to crack detection. Before the composite materials are broken, the force is applied evenly, and it is difficult to produce mechanoluminescence. However, after the material has microcracks, when the same force is applied again, the force on the crack is larger due to the uneven force, and strong mechanoluminescence will be produced to achieve crack detection.
[0037] In order to further illustrate the present invention, the green light mechanoluminescent material provided by the present invention and its preparation method and application are described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0038] Comparative Example 1 A method for preparing a highly efficient green light mechanoluminescent material (without adding Al2O3) without pre-irradiation, the specific steps are as follows: The raw materials H3BO3, Al2O3, CaCO3, Ga2O3 and Tb4O7 are placed in an agate mortar at a molar ratio of 0.002: 0: 5: 3: 0.03, ground for 30 minutes and mixed evenly, then put into an alumina crucible, covered and placed in a box furnace, and sintered at 1200°C for 4 hours. Then the temperature is lowered with the furnace to obtain the luminescent material.
[0039] The mechanoluminescent material obtained in Comparative Example 1 has a chemical formula of Ca3Ga4O9: 0.06Tb 3+ .
[0040] Embodiment 1 The difference from Comparative Example 1 is that the molar ratio of H3BO3, Al2O3, CaCO3, Ga2O3 and Tb4O7 is 0.002: 0.1: 5: 2.9: 0.03, and the remaining steps are consistent with Comparative Example 1.
[0041] The mechanoluminescent material obtained in Example 1, Ca5Ga 6-X Al X O 14 :0.06Tb 3+ , where X=0.2.
[0042] Embodiment 2 The difference from Comparative Example 1 is that the molar ratio of H3BO3, Al2O3, CaCO3, Ga2O3 and Tb4O7 is 0.002: 0.2: 5: 2.8: 0.03, and the remaining steps remain consistent with Comparative Example 1.
[0043] The mechanoluminescent material obtained in Example 2, Ca5Ga 6-X Al X O 14 :0.06Tb 3+ , where X=0.4.
[0044] Embodiment 3 The difference from Comparative Example 1 is that the molar ratio of H3BO3, Al2O3, CaCO3, Ga2O3 and Tb4O7 is 0.002: 0.4: 5: 2.6: 0.03, and the remaining steps remain consistent with Comparative Example 1.
[0045] The mechanoluminescent material obtained in Example 3, Ca5Ga 6-X Al X O 14 :0.06Tb 3+ , where X=0.8.
[0046] Embodiment 4 The difference from Comparative Example 1 is that the molar ratio of H3BO3, Al2O3, CaCO3, Ga2O3 and Tb4O7 is 0.002: 0.6: 5: 2.4: 0.03, and the remaining steps remain consistent with Comparative Example 1.
[0047] Example 4 The mechanoluminescent material obtained, Ca5Ga 6-X Al X O 14 :0.06Tb 3+ , where X=1.2.
[0048] Embodiment 5 The difference from Comparative Example 1 is that the molar ratio of H3BO3, Al2O3, CaCO3, Ga2O3 and Tb4O7 is 0.002: 0.8: 5: 2.2: 0.03, and the remaining steps remain consistent with Comparative Example 1.
[0049] Example 5 The mechanoluminescent material obtained, Ca5Ga 6-X Al X O 14 :0.06Tb 3+ , where X=1.6.
[0050] Performance characterization: Figure 1 The XRD diffraction patterns of the materials of Comparative Example 1 and Examples 1 to 5 are shown. 3+ The amount of ion doping has been increased from Ca3Ga4O9 to Ca5Ga6O 16The incorporation of Al causes the crystal form to change, with some Al ions replacing gallium ions.
[0051] Figure 2 This is a SEM image of the material of Example 4. As can be seen from the image, this material is a columnar crystal.
[0052] Figure 3 The spectra of the materials of Comparative Example 1, Examples 2 to 5 under the same tensile force of 5N are, from bottom to top, Comparative Example 1 (gray), Example 2 (blue), Example 3 (red), Example 5 (yellow) and Example 4 (green); the horizontal axis in the small figure corresponds to Al 3+ The ordinate corresponds to the relative intensity at a wavelength of 544nm. As can be seen from the figure, the main peak of the spectrum is located at 544nm, which belongs to green light emission, indicating that the mesoluminescence intensity of the material is significantly improved after doping with Al2O3. When the doping amount is X = 1.2mol Al 3+ The luminescence performance is best when the light is emitted.
[0053] Figure 4 The following are the actual pictures of the materials of Comparative Example 1 and Example 4 in a ceramic mortar, which were kept in a dark environment and were subjected to sliding tests with a glass rod for 15 consecutive days. The results show that the mesoluminescence of the material of Example 4 is very obvious, and it can still produce mesoluminescence after being placed in the dark for 15 days without charging, indicating that the material has very excellent stability, which is better than that of the material without Al doping. 3+ Compared with the comparative example 1, the mesoluminescence performance is significantly improved.
[0054] Application Example 1 The mechanoluminescent material of Example 4, polydimethylsiloxane (PDMS) and curing agent are fully mixed in a mass ratio of 4: 6: 1 and put into a mold, and then heated at a constant temperature of 70° C. in an oven for 50 minutes to cure and form a mechanoluminescent composite material, which is then applied to crack detection.
[0055] Figure 5 The figure is a test diagram of the mechanoluminescence performance of the composite material in Application Example 1; the small figure is the mechanoluminescence spectrum of the composite material under different forces, from bottom to top, they are the spectra corresponding to 2N~6N. It can be seen from the figure that the main peak of mechanoluminescence is at 544 nanometers, which belongs to Tb 3+ The luminescence of the ions gradually increases with increasing the applied tensile stress intensity (2N~6N), and strong mechanoluminescence is exhibited under a tensile force of 6N.
[0056] Figure 6This is a photo of the mechanoluminescent composite material in Application Example 1. As can be seen from the figure, the mechanoluminescence becomes more obvious as the force increases, and the mechanoluminescence duration reaches 0.183 seconds when the mechanoluminescent composite material is stretched once under a force of 5N.
[0057] Figure 7 This is a scene diagram of the application of mechanoluminescent composite materials for crack detection in Application Example 1. Before the composite material is broken, the force is uniform, and it is difficult to produce mechanoluminescence when a force of 5N is applied. However, after the material has microcracks, when a force of 5N is applied again, the force on the crack is larger due to the uneven force, which will produce strong mechanoluminescence and realize crack detection.
[0058] The present invention adopts the method of 14 :Tb 3+ By doping Al2O3 in the PDMS, a mechanoluminescent material with high mechanoluminescent intensity and excellent stability is obtained, and the preparation method of the invention is simple. The mechanoluminescent material of the invention has very sensitive mechanoluminescence in the powder state and in the composite state with PDMS. The composite material is applied to crack detection and can generate obvious mechanoluminescence under a force of 5N.
[0059] Although the above-mentioned embodiments have made a detailed description of the present invention, they are only some embodiments of the present invention, rather than all embodiments. People can also obtain other embodiments based on the embodiments of the present invention without creative work, and these embodiments all fall within the scope of protection of the present invention.
Claims
1. A green light mechanoluminescent material, characterized in that: The chemical formula is Ca5Ga 6-X Al X O 14 :Tb 3+ , where X=0~1.6, and X is not 0.
2. The green light mechanoluminescent material according to claim 1, characterized in that: The X=0.8~1.
6.
3. The method for preparing the green light mechanoluminescent material according to claim 1 or 2, characterized in that: The following steps are involved: H3BO3, Al2O3, CaCO3, Ga2O3 and Tb4O7 are mixed and calcined to obtain the green light electroluminescent material.
4. The preparation method according to claim 3, characterized in that: The calcination temperature is 1150-1250° C., and the heat preservation time is 3-5 hours.
5. The preparation method according to claim 3 or 4, characterized in that: The molar ratio of H3BO3, Al2O3, CaCO3, Ga2O3 and Tb4O7 is (0.001~0.003): (0.1~0.8): (4.5~5.5): (2.2~2.9): (0.01~0.09).
6. Use of the green mechanoluminescent material according to claim 1 or 2 or the green mechanoluminescent material obtained by the preparation method according to any one of claims 3 to 5 in crack detection.
7. A mechanoluminescent composite material, characterized in that: Including the following raw materials by mass: 3-5 parts of green light luminescent material, 5-7 parts of molding agent and 0.9-1.1 parts of curing agent; The green mechanoluminescent material is the green mechanoluminescent material according to claim 1 or 2 or the green mechanoluminescent material obtained by the preparation method according to any one of claims 3 to 5.
8. The mechanoluminescent composite material according to claim 7, characterized in that: The molding agent includes polydimethylsiloxane and / or epoxy resin.
9. The method for preparing the mechanoluminescent composite material according to claim 7 or 8, characterized in that: The following steps are involved: The green light mechanoluminescent material, the molding agent and the curing agent are mixed and cured to obtain the mechanoluminescent composite material.
10. The preparation method according to claim 9, characterized in that: The curing temperature is 65-75° C. and the curing time is 40-60 minutes.
Citation Information
Patent Citations
Green light luminescent material and preparation method thereof
CN101921591A
Aluminum gallate-based fluorescent material and preparation method thereof
CN105778904A
Nitride luminescent material and luminescent device containing same
CN107974252A
Rare earth ion doped gallate reversible photochromic material, and preparation method and application thereof
CN108913131A
Green light long-afterglow luminescent materials and preparation method thereof
CN109370579A
